2013
DOI: 10.3906/sag-1205-135
|View full text |Cite
|
Sign up to set email alerts
|

Haematological changes in malaria-infected children in North-West Nigeria

Abstract: Neodymium-titania/silica films were prepared by the sol-gel method with the addition of various amounts of hydroxy propyl cellulose (HPC) and 5.09 × 10 −5 g g −1 solution of carboxy methyl cellulose (CMC) in saturated conditions. The porous Nd-TiO 2 /SiO 2 was obtained after heat treatment for 2 h at 500 • C, with the surface area up to 276 m 2 g −1 , which was measured using the Brunauer, Emmett, and Teller (BET) method. Scanning electron microscopy (SEM) showed that the particle size of Nd-TiO 2 /SiO 2 decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…Malarial infection causes changes in haematological and biochemical parameters of affected individuals to varying degrees resulting in changes in body physiology [4,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malarial infection causes changes in haematological and biochemical parameters of affected individuals to varying degrees resulting in changes in body physiology [4,17].…”
Section: Discussionmentioning
confidence: 99%
“…It is endemic in 100 countries making about half of the world's population to be at risk [3]. About 50% of Nigerian population is reported to suffer from at least one episode of malaria each year [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the linear regression model, it was observed that ITN use had a signi cant in uence on WBC, Hb, RBC, Hct, MCHC, RDW-CV and Plt. The signi cantly higher Hb, RBC, MCHC, RDW-CV and Plt count in ITN users than non-users, may be as a result of the protective e cacy of the ITNs that prevents the ITN users from the bite of the Anopheles vector thereby preventing them from contracting the Plasmodium infection, which has been proven in several studies [58,61,62] to reduce the haematological parameters of children. This nding corroborates with results of Maina et al [61] and Kotepui et al [59] who reported that; red blood cell counts, haemoglobin and platelets counts were signi cantly lower in malaria positive children than negative children.…”
Section: Malaria Parasite Itn Knowledge and Haematological Indicesmentioning
confidence: 95%
“…Most times disease conditions such as malaria tend to influence haematological parameters, which presents itself with various clinical presentations depending on the severity of the infection on the human body. During the pathogenesis of malaria infection in the body of humans, some of the complications that usually occur include haematological changes that involve the major cell types such as red blood corpuscles (RBCs), leucocytes and thrombocytes [2,3]. Quite a numbers of malaria induced complications that includes anaemia, thrombocytopaenia and leukocytosis have been established [4].…”
Section: Introductionmentioning
confidence: 99%